(3OjhGf HgGA GdOjf Ydi Hf GdSGYGJis - (3Ydj Hf eMeO Hf QSJe Hf gQOhR, CHh GdMSf, HgGA GdOjf GHf GdSGYGJj,J (B604 (3g` s ((3Ydi Hf eMeO GdeQJVi GdShOi GdRjOi GdYOdi s)
(3ChdgG (B:s
(3Chd GdehLhO efg (B: (3Sh CHb heYi GdMeQ ajgG eZjQI hef bHd cGfJ ai Gdcejf ef GdTgH s
(3BNQgG (B:s
(3Ef JMGda ai CfgG GdTeS aCfXQ fhQgG ChLOJ bd GdCbeGQ Je ZRd OjhGf HgGA GdOjf Ydi Hf GdSGYGJi HMeO Gddg hYhfg s
(3HgG fXGe GdJYbjHIs
(3jJdhg eNJGQGJ TYQjI ChdgG ef OjhGf GHf eYdes
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B330 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B62s
Keywords: (3GdCOHs